Genetically modified rabies virus vector‐based bovine ephemeral fever virus vaccine induces protective immune responses against BEFV and RABV in mice. Issue 3 (5th September 2020) - Zheng, Wenwen; Zhao, Zhongxin; Tian, Li; Liu, Lele; Xu, Tong; Wang, Xianwei; He, Hongbin; Xia, Xianzhu; Zheng, Ye; Wei, Yurong; Zheng, Xuexing
Abstract: Bovine ephemeral fever (BEF), caused by the bovine ephemeral fever virus (BEFV), is associated with an acute febrile infection in cattle and widespread in tropical and subtropical areas, leading to great economic losses to cattle and milk industry. However, no efficacious BEF vaccine is currently available in China. Herein, we generated a recombinant rabies virus (RABV) expressing BEFV glycoprotein (LBNSE‐BG), utilizing a reverse genetics system based on the recombinant rabies virus strain LBNSE. It was found that mice immunized with LBNSE‐BG produced robust neutralizing antibodies against both BEFV and RABV, and developed complete protection from lethal RABV challenge. Further studies showed that LBNSE‐BG activated more dendritic cells (DCs), B cells and T cells in immunized mice than the parent virus LBNSE. Collectively, these findings demonstrate that the recombinant LBNSE‐BG described here has the potential to be developed as a cost‐effective and efficacious bivalent vaccine for cattle use in endemic areas of BEF and rabies.